Hadith #105 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said. No doubt your blood, property, the sub-narrator Muhammad thought that Abu Bakra had also mentioned and your honor (chastity), are sacred to one another as is the sanctity of this day of yours in this month of yours. It is incumbent on those who are present to inform those who are absent.â (Muhammad the Sub-narrator used to say, âAllahâs Messenger (ï·º) told the truth.â) The Prophet (ï·º) repeated twice: âNo doubt! Havenât I conveyed Allahâs message to you.
Grade: Sahih

Hadith #766 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
I reached the Prophet (ï·º) in the mosque while he was bowing in prayer and I too bowed before joining the row mentioned it to the Prophet (ï·º) and he said to me, âMay Allah increase your love for the good. But do not repeat it again (bowing in that way).
Grade: Sahih

Hadith #1012 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
We were with Allahâs Messenger (ï·º) when the sun eclipsed. Allahâs Messenger (ï·º) stood up dragging his cloak till he entered the Mosque. He led us in a two-rak`at prayer till the sun (eclipse) had cleared. Then the Prophet (p.b.u.h) said, âThe sun and the moon do not eclipse because of someoneâs death. So whenever you see these eclipses pray and invoke (Allah) till the eclipse is over.â
Grade: Sahih

Hadith #1020 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said: âThe sun and the moon are two signs amongst the signs of Allah and they do not eclipse because of the death of someone but Allah frightens His devotees with them.â
Grade: Sahih

Hadith #1032 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
In the lifetime of the Prophet (ï·º) the sun eclipsed and then he offered a two rak`at prayer.
Grade: Sahih

Hadith #1033 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
In the lifetime of the Allahâs Messenger (ï·º) (p.b.u.h) the sun eclipsed and he went out dragging his clothes till he reached the Mosque. The people gathered around him and he led them and offered two rak`at. When the sun (eclipse) cleared, he said, âThe sun and the moon are two signs amongst the signs of Allah; they do not eclipse because of the death of someone, and so when an eclipse occurs, pray and invoke Allah till the eclipse is over.â It happened that a son of the Prophet (ï·º) ca
Grade: Sahih

Hadith #1679 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) delivered to us a sermon on the Day of Nahr. He said, âDo you know what is the day today?â We said, âAllah and His Apostle know better.â He remained silent till we thought that he might give that day another name. He said, âIsnât it the Day of Nahr?â We said, âIt is.â He further asked, âWhich month is this?â We said, âAllah and His Apostle know better.â He remained silent till we thought that he might give it another name. He then said, âIsnât it t
Grade: Sahih

Hadith #1811 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe terror caused by Al-Masih Ad-Dajjal will not enter Medina and at that time Medina will have seven gates and there will be two angels at each gate guarding them.â
Grade: Sahih

Hadith #1844 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe two months of `Id i.e. Ramadan and Dhul-Hijja, do not decrease (in superiority).
Grade: Sahih

Hadith #2097 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âDonât sell gold for gold unless equal in weight, nor silver for silver unless equal in weight, but you could sell gold for silver or silver for gold as you like.â
Grade: Sahih

Hadith #2549 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said thrice, âShould I inform you out the greatest of the great sins?â They said, âYes, O Allahâs Messenger (ï·º)!â He said, âTo join others in worship with Allah and to be undutiful to oneâs parents.â The Prophet (ï·º) then sat up after he had been reclining (on a pillow) and said, âAnd I warn you against giving a false witness, and he kept on saying that warning till we thought he would not stop. (See Hadith No. 7, Vol. 8)
Grade: Sahih

Hadith #2557 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
A man praised another man in front of the Prophet (ï·º) . The Prophet (ï·º) said to him, âWoe to you, you have cut off your companionâs neck, you have cut off your companionâs neck,â repeating it several times and then added, âWhoever amongst you has to praise his brother should say, âI think that he is so and so, and Allah knows exactly the truth, and I do not confirm anybodyâs good conduct before Allah, but I think him so and so,â if he really knows what he says about him.â
Grade: Sahih

Hadith #3064 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said. â(The division of time has turned to its original form which was current when Allah created the Heavens and the Earths. The year is of twelve months, out of which four months are sacred: Three are in succession Dhul-Qaâ da, Dhul-Hijja and Muharram, and (the fourth is) Rajab of (the tribe of) Mudar which comes between Jumadi-ath-Thaniyah and Sha ban.â
Grade: Sahih

Hadith #3366 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âDo you think that the tribes of Juhaina, Muzaina, Aslam and Ghifar are better than the tribes of Bani Tamim, Bani Asad, Bani `Abdullah bin Ghatafan and Bani Amir bin Sasaa?â A man said, âThey were unsuccessful and losers.â The Prophet (ï·º) added, â(Yes), they are better than the tribes of Bani Tamim, Bani Asad, Bani `Abdullah bin Ghatafan and Bani Amir bin Sasaa.â
Grade: Sahih

Hadith #3367 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Al-Aqraâ bin Habis said to the Prophet (ï·º) âNobody gave you the pledge of allegiance but the robbers of the pilgrims (i.e. those who used to rob the pilgrims) from the tribes of Aslam, Ghifar, Muzaina.â (Ibn Abi Yaâqub is in doubt whether Al-Aqraâ added. âAnd Juhaina.â) The Prophet (ï·º) said, âDonât you think that the tribes of Aslam, Ghifar, Muzaina (and also perhaps) Juhaina are better than the tribes of Bani Tamim, Bani Amir, Asad, and Ghatafan?â Somebody said, âThey
Grade: Sahih

Hadith #3474 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Once the Prophet (ï·º) brought out Al-Hasan and took him up the pulpit along with him and said, âThis son of mine is a Saiyid (i.e. chief) and I hope that Allah will help him bring about reconciliation between two Muslim groups.â
Grade: Sahih

Hadith #3583 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
I heard the Prophet (ï·º) talking at the pulpit while Al-Hasan was sitting beside him, and he (i.e. the Prophet ) was once looking at the people and at another time Al-Hasan, and saying, âThis son of mine is a Saiyid (i.e. chief) and perhaps Allah will bring about an agreement between two sects of the Muslims through him.â
Grade: Sahih

Hadith #4212 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âTime has taken its original shape which it had when Allah created the Heavens and the Earth. The year is of twelve months, four of which are sacred, and out of these (four) three are in succession, i.e. Dhul-Qaâda, Dhul-Hijja and Al-Muharram, and the fourth is Rajab which is named after the Mudar tribe, between (the month of) Jumaida (ath-thania) and Shaâban.â Then the Prophet (ï·º) asked, âWhich is this month?â We said, âAllah and His Apostle know better.â
Grade: Sahih

Hadith #4231 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
During the days (of the battle) of Al-Jamal, Allah benefited me with a word I had heard from Allahâs Apostle after I had been about to join the Companions of Al-Jamal (i.e. the camel) and fight along with them. When Allahâs Messenger (ï·º) was informed that the Persians had crowned the daughter of Khosrau as their ruler, he said, âSuch people as ruled by a lady will never be successful.â
Grade: Sahih

Hadith #5337 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âTime has come back to its original state which it had on the day Allah created the Heavens and the Earth. The year is twelve months, four of which are sacred, three of them are in succession, namely Dhul-Qaâda, Dhul Hijja and Muharram, (the fourth being) Rajab Mudar which is between Jumaâda (ath-thamj and Shaâban. The Prophet (ï·º) then asked, âWhich month is this?â We said, âAllah and his Apostle know better.â He kept silent so long that we thought that
Grade: Sahih

Hadith #5559 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The solar eclipse occurred while we were sitting with the Prophet (ï·º) He got up dragging his garment (on the ground) hurriedly till he reached the mosque The people turned (to the mosque) and he offered a two-rak`at prayer whereupon the eclipse was over and he traced us and said, âThe sun and the moon are two signs among the signs of Allah, so if you see a thing like this (eclipse) then offer the prayer and invoke Allah till He remove that state.â
Grade: Sahih

Hadith #5748 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said thrice, âShall I not inform you of the biggest of the great sins?â We said, âYes, O Allahâs Messenger (ï·º)â He said, âTo join partners in worship with Allah: to be undutiful to oneâs parents.â The Prophet (ï·º) sat up after he had been reclining and added, âAnd I warn you against giving forged statement and a false witness; I warn you against giving a forged statement and a false witness.â The Prophet kept on saying that warning till we thought
Grade: Sahih

Hadith #5832 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
A man was mentioned before the Prophet (ï·º) and another man praised him greatly The Prophet (ï·º) said, âMay Allahâs Mercy be on you ! You have cut the neck of your friend.â The Prophet (ï·º) repeated this sentence many times and said, âIf it is indispensable for anyone of you to praise someone, then he should say, âI think that he is so-and-so,â if he really thinks that he is such. Allah is the One Who will take his accounts (as He knows his reality) and no-one can sanctify anybody
Grade: Sahih

Hadith #5929 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
A man praised another man in front of the Prophet. The Prophet (ï·º) said thrice, âWailaka (Woe on you) ! You have cut the neck of your brother!â The Prophet (ï·º) added, âIf it is indispensable for anyone of you to praise a person, then he should say, âI think that such-and-such person (is so-and-so), and Allah is the one who will take his accounts (as he knows his reality) and none can sanctify anybody before Allah (and that only if he knows well about that person.)â.
Grade: Sahih

Hadith #6038 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Allahâs Messenger (ï·º) said, âShall I inform you of the biggest of the great sins?â They said, âYes, O Allahâs Apostle!â He said, âTo join partners in worship with Allah, and to be undutiful to oneâs parents. â
Grade: Sahih

Hadith #6393 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âDo you think if the tribes of Aslam, Ghifar, Muzaina and Juhaina are better than the tribes of Tamim, âAmir bin Saâsaâa, Ghatfan and Asad, they (the second group) are despairing and losing?â They (the Prophetâs companions) said, âYes, (they are).â He said, âBy Him in Whose Hand my soul is, they (the first group) are better than them (the second group).
Grade: Sahih

Hadith #6663 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet. said, âThe biggest of the great sins are: To join others in worship with Allah, to be undutiful to oneâs parents, and to give a false witness.â He repeated it thrice, or said, ââ¦.a false statement,â and kept on repeating that warning till we wished he would stop saying it. (See Hadith No.7, Vol. 8)
Grade: Sahih

Hadith #6813 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Allahâs Messenger (ï·º) addressed the people saying, âDonât you know what is the day today?â They replied, âAllah and His Apostle know better.â We thought that he might give that day another name. The Prophet said, âIsnât it the day of An-Nahr?â We replied, âYes. O Allahâs Messenger (ï·º).â He then said, âWhat town is this? Isnât it the forbidden (Sacred) Town (Mecca)?â We replied, âYes, O Allahâs Messenger (ï·º).â He then said, âYour blood, your properties,
Grade: Sahih

Hadith #6834 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
During the battle of Al-Jamal, Allah benefited me with a Word (I heard from the Prophet). When the Prophet heard the news that the people of the Persia had made the daughter of Khosrau their Queen (ruler), he said, âNever will succeed such a nation as makes a woman their ruler.â
Grade: Sahih

Hadith #6856 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âThe terror caused by Al-Masih Ad-Dajjal will not enter Medina and at that time Medina will have seven gates and there will be two angels at each gate (guarding them).
Grade: Sahih

Hadith #6857 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
Grade: Sahih

Hadith #7162 - Sahih al-Bukhari - Abu Bakra al-Thaqafi (Sahih al-Bukhari)
The Prophet (ï·º) said, âTime has come back to its original state which it had when Allah created the Heavens and the Earth, the year is twelve months, of which four are sacred; (and out of these four) three are in succession, namely, Dhul-Qaâda, Dhul-Hijja and Muharram, and (the fourth one) Rajab Mudar which is between Jumad (Ath-Tham) and Shaâban.â The Prophet (ï·º) then asked us, âWhich month is this?â We said, âAllah and His Apostle know (it) better.â He kept quiet so long th
Grade: Sahih